Combined Effect of Temperature and Light on the Egg Hatchability in Pomaceae Canaliculata (Gastropoda: Ampuliriidae) From Malaysia / Hasnun Nita Ismail... [et al.] - Ismail, Hasnun Nita; Mazlan, Mohd Fadli; Ahmad Fajri, Faris Aizat; Syed Ihsan, Syed Amir Irfan; Musa, Nadia Nisha (Universiti Teknologi MARA, Negeri Sembilan, 2019)
The Golden Apple Snail (GAS), Pomacea canaliculata is an invasive species that has become a serious pest organism in rice fields in Southeast Asia since 1980s. This study was conducted to assess the hatchability of eggs under a combination effect of temperature and light. The clusters of eggs were exposed to different temperature (28 o C, 30 o C, 32 o C, 34 o C and 36 o C) and under the presence and the absence of light. The finding showed that the cluster of egg hatched faster with an increase of temperature (2-way ANOVA; P < 0.05). However, the egg hatchability was not impacted by the presence or the absence of light. The combined effect between temperature and light on egg hatchability was also insignificant (2-way ANOVA; P > 0.05). Our findings indicate that temperature alone produces the main impact on the egg hatchability. Therefore, this knowledge provides an initial understanding to predict the population dynamic and geographical distribution of Pomacea from Malaysia particularly in the effort to hamper their ecological invasion.